Status Gizi dan Pemberian Kapsul Vitamin A sebagai Faktor Risiko Pneumonia Balita Usia 18-59 Bulan: Nutritional Status and Provision of Vitamin A as Risk Factors for Pneumonia among Toddlers Age 18-59 Months - Novarianti, Wiji; Syukri, Muhammad; Izhar, M. Dody; Ridwan, M; Faisal, Faisal (Poltekkes Kemenkes Palu, 2021)
Introduction: Pneumonia accounts for 16 % of the causes of death in children under five including in Indonesia. This study aims to determine nutritional status, provide vitamin A capsules, and complete immunization as risk factors for pneumonia in toddlers aged 18-59 months. Methods: This study used a case-control design with 47 cases and 47 control children. The case was a toddler with pneumonia aged 18-59 months who was registered at Puskesmas Paal V Jambi City. Controls were toddlers who did not experience pneumonia with age (range â‰¤3 months), gender, and came from the same sub-district as the case toddler. Sampling was done by purposive technique by selecting the latest patient medical record data. Data collection was carried out by interview method in October-November 2020. Data analysis was carried out univariate and bivariate using the Chi-Square test. Results: The results showed nutritional status (p=0.023 OR=3.93 95% CI 1.29-11.96), Vitamin A capsules administration (p=0.026 OR=3.12 95% CI 1.23-7.91) is a risk factor for pneumonia in children under-five. Complete immunization is nor a risk factor for pneumonia in children under five. Conclusion: The conclusion of the study was nutritional status and vitamin A administration as risk factors for pneumonia in children aged 18-59 months.